PERANCANGAN DAN SIMULASI FRAME MOBIL GOKART - Ramadhan, Muhammad Syahrul; Mangalla, Lukas Kano; Samhuddin, Samhuddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
This research isaimingto know the distribution of stress, strain, displacementas well as safety factor on gmokart frame. The frame was designed in Autodesk inventor software and simulated using AnsysFluent. Carbon steel with maximum loadof 95 Kg was used as material for the frame. The results of this research indicate that maximum stress at the main frame can reach around 34,731 N/m2 in simulation and 34,772 N/m2 by manual calculation. On the other hand, the maximum stresscan reach 1,95 ×  cm in  simulation and 1,73×  from manual calculation. The maximum displacementhappened on the frame is around 0,175 cm in simulation while in calculation it can reach around 0,278 cm. Material used for the frame has the safety factor of 10,045.Keyword: Design, simulation, frame, gokart, and savety factor.